In-Hospital Mortality Risk Factors among Hospitalized Geriatric Patients: A Cohort Study on Tertiary Referral Hospital in Indonesia - Yofi, Fadhil Abiyyu; Damayanti, Arlia Ayu; Widajanti, Novira (Jurnal Penyakit Dalam Indonesia, 2021)
Introduction. Decreasing fertility rates and increasing life expectancy cause an increase in the population of the elderly, with the number of elderly in the world is estimated to increase from 9.3% in 2020 to 16.0% in 2050. 24.35% of the elderly in Indonesia experience illness, and 8.71% have been hospitalized in one year. This study aimed to determine the risk factors for the death of elderly who were hospitalized.